2009
DOI: 10.1089/ham.2008.1104
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the Muscle Proteome to Exercise at Altitude

Abstract: The ascent of humans to the summits of the highest peaks on Earth initiated a spurt of explorations into the physiological consequences of physical activity at altitude. The past three decades have demonstrated that the resetting of respiratory and cardiovascular control with chronic exposure to altitudes above 4000 m is accompanied by important structural-functional adjustments of skeletal muscle. The fully altitude-adapted phenotype preserves energy charge at reduced aerobic capacity through the promotion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 89 publications
1
59
0
2
Order By: Relevance
“…However, it was shown that VEGF levels in muscle interstitium increased 3 and 8 h post a high-volume endurance exercise (Flueck 2009;Hoier et al 2010). The authors concluded that exercise causes a secretion of VEGF from human skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that VEGF levels in muscle interstitium increased 3 and 8 h post a high-volume endurance exercise (Flueck 2009;Hoier et al 2010). The authors concluded that exercise causes a secretion of VEGF from human skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HIF-1α and COX4I2 transcripts and HIF-1α protein is thought to represent markers of tissue hypoxia [22]. We reported before that their expression in vastus lateralis muscle after endurance type bicycle exercise is markedly affected by ambient hypoxia [16], which is known to produce a further lowering of tissue oxygenation [17]. This finding compares to a higher gene expression for components of mitochondrial respiration and Krebs cycle with the lowering of levels in metabolically active yeast [23].…”
Section: Discussionmentioning
confidence: 92%
“…We therefore wished to assess the interaction of genetical and pharmacological inhibition of ACE on muscle transcript expression post-exercise. We specifically hypothesized that hypoxia-sensitive transcript expression of isoform 1 and 2 of subunit 4 of cytochrome c oxidase, COX4I1 and COX4I2, and HIF-1α transcript and protein [14][15][16], would show ACE-dependent level alterations in knee extensor muscle during recovery from cycle-type endurance exercise as this lowers muscle oxygenation in relation to capillary perfusion [17].…”
Section: Transcript Expressionmentioning
confidence: 99%
“…The adaptations of muscle in humans exposed to high altitude have been extensively studied and the overall consensus is that muscle adapts to high altitude hypoxia by a decrease in oxidative capacity, whereas combined with exercise training, muscle OXPHEN may even improve [6,33,34]. In addition, numerous experiments have been conducted in which rodents were exposed to chronic hypoxia and in some of these studies, a relative loss of muscle OXPHEN was indeed found, but not in others.…”
Section: Hypoxia and Maintenance Of Muscle Metabolismmentioning
confidence: 99%